Problematika Keluarga dan Solusi Penanganannya - Bunga Sovia Erik; Afriliani Afriliani; Hidayani Syam (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
The writing of this journal is motivated by family problems in Indonesia, which include financial problems, poor communication, parenting, work-life balance, quarrels, division of household chores, and lack of appreciation. The solution to overcome this problem is to improve communication, share tasks, and appreciate each other. This research is a qualitative research that is library-based (Library Research) using descriptive analysis. The results show that family problems are challenges that can affect family harmony and well-being, such as conflict, financial problems, domestic violence, and differences in perspective on child education. To overcome them, effective communication, conflict management skills, and appropriate approaches, such as psychodynamic, behavioral, and counseling, are needed, so that families can find solutions to achieve a happier and more balanced life.